2005
DOI: 10.1159/000090346
|View full text |Cite
|
Sign up to set email alerts
|

CadC-Mediated Activation of the <i>cadBA</i> Promoter in <i>Escherichia coli</i>

Abstract: The transcriptional activator CadC in Escherichia coli, a member of the ToxR-like proteins, activates transcription of the cadBA operon encoding the lysine decarboxylase CadA and the lysine-cadaverine antiporter CadB. cadBA is induced under conditions of acidic external pH and exogenous lysine; anoxic conditions raise the expression level up to 10 times. To characterize the binding mechanism of CadC, procedures for the purification of this membrane-integrated protein and its reconstitution into proteoliposomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 71 publications
(45 reference statements)
6
103
0
Order By: Relevance
“…Expression of BcrR in E. faecalis and E. coli-To study membrane-bound DNA-binding proteins, DNA binding assays have been either performed with inverted membrane vesicles that may contain other potentially contaminating proteins (10,35), soluble variants of the protein (36,37), in the presence of detergent (38), or by reconstitution of purified protein into liposomes (39). The level of BcrR expression in native membranes of E. faecalis was too low for EMSAs with bcrABD promoter DNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of BcrR in E. faecalis and E. coli-To study membrane-bound DNA-binding proteins, DNA binding assays have been either performed with inverted membrane vesicles that may contain other potentially contaminating proteins (10,35), soluble variants of the protein (36,37), in the presence of detergent (38), or by reconstitution of purified protein into liposomes (39). The level of BcrR expression in native membranes of E. faecalis was too low for EMSAs with bcrABD promoter DNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…These include a low ratio of protein-to-lipid in the proteoliposomes, BcrR His orientated in the opposite direction with the DNA-binding domain on the inside of the proteoliposomes, and potential clumping of proteoliposomes preventing BcrR His from accessing target DNA. Previously described EMSAs with proteoliposomes have also required large quantities of protein to DNA for similar reasons (39).…”
Section: Sds-page Analysismentioning
confidence: 99%
“…Its altogether 11 a-helices (nos. [4][5][6][7][8][9][10][11][12][13][14] are organized as a bundle of five antiparallel a-helical pairs, whereby helix 13 comprises just one turn. These pairs are twisted in a clockwise direction, resulting in a spiral bundle such that the C-terminus of helix 4 is situated close to the N-terminal end of helix 12.…”
Section: Resultsmentioning
confidence: 99%
“…12 The DNA-binding sites were identified and the interaction between purified CadC and the promoter region was demonstrated in vitro. 13 Expression of the cadBA operon is activated at low external pH and concomitantly available lysine. Recently, it was shown that CadC is not a direct sensor of the external lysine concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The cadBA operon encodes lysine decarboxlase (CadA) and lysine-cadaverine antiporter (CadB). The expression of the cadBA operon is dependent upon the transcriptional activator CadC (8,9,11,12,16,22). CadA has a pH optimum of 5.7 and converts lysine into cadaverine and CO 2 (19).…”
Section: Smentioning
confidence: 99%